Analisis Potensi Dan Pengembangan Desa Wisata Melalui Badan Usaha Milik Desa (BUMDES) : Studi Kasus Wisata Sawah Sabarang Desa Padang Bulan Kabupaten Mandailing Natal - Zein Lubis, Sari Purnama; Nawawi, Zurinal M.; Syahbudi, Muhammad (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Sabarang rice field tourism is in a very strategic area as a tourist destination because, its location located on the Sumatra Causeway (Bukittinggi-Padang Sidempuan) can be an attraction factor for tourists to visit. This study aims to: 1). Find out the tourism potential of sabarang rice fields through the Padang Bulan Mandailing Natal Regency miik Village enterprise (BUMDes). 2). Knowing the development of sabarang rice field attractions through BUMDes Padang Bulan village, Kotanopan District, Mandailing Natal Regency. 3). Knowing the results of the analysis of the potential and development of sawah sabarang Tourism Village through BUMDes Padang Bulan Village Mandailing Natal Regency with SWOT analysis. In this study the methods used are qualitative methods and data obtained using SWOT analysis. The results showed that : 1). Sabarang Rice Field tourism Padang Bulan Village Mandailing Natal Regency has a natural potential that is still very beautiful in the form of a vast expanse of rice fields, forests, waterfalls and also crossed by the Batang Gadis River. Then the place is strategic as a tourist destination because, its location is located on Jalan Lintas Sumatera (Bukittinggi-Padang Sidempuan) which is an attraction factor for tourists to visit. 2). efforts to develop the Sabarang Rice Field tourism object in Padang Bulan Village are how to achieve the empowerment of Tourism objects in Padang Bulan Village and can also obtain village revenue through the sabarang rice field tourism object also the padang bulan village government hopes that people who have household industries that have received training can market their products in sabarang rice field tourism and of course sabarang rice field tourism can open as many jobs as possible for young people and the Padang Bulan village community. 3). Based on SWOT analysis shows that sabarang rice field tourism is in a good position that is aggressive / developing (SO strategy). Where this position in a business has a strong position and the opportunity to grow. The strategy that must be implemented for tourism in this position is to support aggressive growth policies.